Strategy for Fulfill Beef Demand in Samarinda Through Development of Livestock Stakeholder Potential - Muzaqi, K.; H. Nuraini; L. Cyrilla E. N. S. D.; B. W. Putra (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
The demand for beef as a source of animal protein in Samarinda City continues to increase in line with population growth and changes in consumption patterns. However, local production has not been able to meet the demand, leading to a heavy reliance on external supplies, which poses a major challenge. This study aims to analyze the potential development of livestock stakeholders to achieve self-sufficiency in meeting beef demand. Using a survey method, data were collected through interviews, observations, and questionnaires involving forty nine respondents, including farmers, slaughterhouses, government representatives, traders, and consumers. The analysis, using the Strengths, Opportunities, Aspirations, Results (SOAR) approach, reveals that optimizing stakeholder potential such as enhancing farmer capacity, modernizing production facilities, and fostering synergy between the government and the private sector can improve the independence and sustainability of the livestock sector. The formulated strategies include restricting livestock traffic from outside the region, strengthening farmer capacity, and enhancing facilities and stakeholder collaboration. The implementation of these strategies expected to support food security, stabilize prices, and reduce dependence on external supplies.